PERAN INTELLECTUAL CAPITAL PADA KEUNGGULAN KOMPETITIF UMKM MELALUI PEROLEHAN SUMBER DAYA (Studi Pada UMKM Souvenir Di Solo Raya) - Rosita, Rosita; Susanto, Heri; Kusasih, Ida Ayu Kade Rachmawati; Wulandari, Amy; Ardi, Rudi Prasetyo (EKOBIS, 2023)
MSMEs should have the resources to survive and develop in the long term. The resources required can be tangible or intangible resources. This research examines the influence of the owner's Intellectual Capital (IC) on the acquisition of resources which will then influence sustainable competitive advantage. The respondents used were MSMEs making wooden souvenirs from 7 cities, namely Surakarta, Sragen, Sukoharjo, Wonogiri, Klaten, Boyolali and Karanganyar. From the 120 MSMEs who were respondents, the results showed that Intellectual Capital had a significant effect on sustainable competitive advantage, Intellectual Capital had a significant effect on Resource Acquisition, Resource acquisition had a significant effect on sustainable competitive advantage, and Intellectual Capital (IC) through resource acquisition had no significant effect towards Sustainable Competitive Advantage.